2013
DOI: 10.3109/00365513.2013.819524
|View full text |Cite
|
Sign up to set email alerts
|

Higher extracellular fluid volume in women is concealed by scaling to body surface area

Abstract: Lean tissue in women contains more extracellular water than in men, a difference that is obscured by scaling to BSA. The likely problem with BSA is its insensitivity to body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Hyponatremia was commoner and more severe in males in this study. This finding is in disagreement with a previous study that found hyponatremia commoner in females [16]. It is however in agreement with Mannheimer et al who reported that hyponatremia and comorbidities associated with it are commoner in men [17].…”
Section: Discussioncontrasting
confidence: 96%
“…Hyponatremia was commoner and more severe in males in this study. This finding is in disagreement with a previous study that found hyponatremia commoner in females [16]. It is however in agreement with Mannheimer et al who reported that hyponatremia and comorbidities associated with it are commoner in men [17].…”
Section: Discussioncontrasting
confidence: 96%
“…The convention of indexing glomerular filtration rate to BSA attempts to normalize kidney function across populations of differing body size but may be inappropriate when a more precise estimation of kidney function is needed or in patients with extreme body sizes. Adding to the complexity, there is a disproportionate relation between extracellular volume (ESV) and BSA [ 40 ], and a higher ECV in women may be concealed by scaling to BSA [ 41 ]. The use of absolute values has been shown to improve the performance of estimation of individual kidney function [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their data suggested that scaling UF rate to body mass would result in a very uneven level of risk if a single target were chosen for both men and women divided by body mass (6). For example, the average UF rate in the cohort was 13 ml/kg/hr, and the risk (31). Of interest, the ECV/BSA relationship was more consistent across quintiles of BMI than ECV/weight, but ECV scaled to body surface area was slightly (7%) higher, while ECV scaled to lean body was slightly (9%) lower, in men than in women.…”
Section: Scaling Arguments Based On Outcomes Datamentioning
confidence: 91%
“…Relationship between ECV /Weight and the quintile of body mass index according to data from Peters et al. . Of interest, the ECV / BSA relationship was more consistent across quintiles of BMI than ECV /weight, but ECV scaled to body surface area was slightly (7%) higher, while ECV scaled to lean body was slightly (9%) lower, in men than in women.…”
Section: Extracellular Fluid Volumementioning
confidence: 99%